Mengembangkan Program Sosial Media & Pengetahuan Tanggapan Bencana Alam (BPBD) Untuk SLB Harapan Bunda Kota Surabaya - Rere Isa Shangpari Musti; Putra Yudha; Maghiesswara Bayu W.J; Mistika Ayu Wulandari; Lucky Cahyo Kurniawan; Moch. Arkansyah; Anita Agustina Wulandari (LPPM Stikosa - AWS, 2024)
Developing a Social Media & Natural Disaster Response Knowledge Program for SLB Harapan Bunda is a task that will be carried out by students from stikosa-AWS as participants in the 6th semester of the KKL. On March 22, an unfortunate event occurred, namely a natural disaster in the form of an earthquake. The program that we will carry out and the title was chosen because we, as participants in KKL group 4, will provide education and understanding about responsiveness in dealing with natural disasters. Natural disasters are not only limited to earthquakes, but also include other examples such as tsunamis, landslides, volcanic eruptions, floods, fires, and others. So, group 4 of the Stikosa-AWS KKL participants will carry out tasks that involve the application of knowledge gained in higher education to teach or apply it to the general public in the context of communication. The relationship between communication and response to disasters is that by providing knowledge about disasters, it is hoped that SLB Harapan Bunda can provide direction to students with the understanding that has been given. In addition, it is hoped that the public can also gain understanding through social media that has contained educational content about disaster response. The importance of effective communication is that it leads to good understanding, while poor communication can lead to incomprehension.